Multiple Intraventricular Non-Hodgkin Lymphoma – A Rare Case Report - Hossain, Mohammad Nazrul; Rashid, Mohammad. Humayun; Mamun, Abdullah Al; Hasan, Mahmudul (Bangladesh Journal of Neurosurgery, 2021)
Lymphoma of the central nervous system can present with a wide variety of clinical symptoms and imaging characteristics which can be challenging for radiologist as well as neurosurgeons to deal with. Primary CNS lymphoma (PCNSL) accounts for 1% of all primary brain tumors which is a rare variant of extranodal non-Hodgkin’s lymphoma. We report a case primary central nervous system Non-Hodgkins lymphoma presenting a multiple intraventricular and periventricular masses in a 14 years young man with severe headache, convulsion and unsteady gait. The diagnosis was obtained by image guided surgical biopsy. This is an unusual presentation of primary central nervous system lymphoma involving lateral ventricle and 3rd ventricle while the majority of the case presenting as solitary masses. Bang. J Neurosurgery 2021; 10(2): 206-209